2005
DOI: 10.1007/bf02710273
|View full text |Cite
|
Sign up to set email alerts
|

Metastases in the sphenoidal sinus in a patient with papillary thyroid cancer

Abstract: Tumours that produce metastases in the paranasal sinuses or sphenoidal sinus are rare; the carcinomas of kidney and lung being the most frequent with this type of metastasis. Distant metastases from differentiated thyroid carcinoma are rare and, moreover, when they metastasize, they do so into lung and bone. We report a patient who had a papillary thyroid carcinoma with metastases into the sphenoidal sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Synchronous or simultaneous tumors of the head and neck and the lung are seen in 31% incidence in these cases. 7 Therefore, discrimination of second primary or metastatic tumors should be done in patients with lung malignancies before any decisions on treatment modality. Several criteria are described for determination of second primary or metastatic disease, but none of these is certain.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous or simultaneous tumors of the head and neck and the lung are seen in 31% incidence in these cases. 7 Therefore, discrimination of second primary or metastatic tumors should be done in patients with lung malignancies before any decisions on treatment modality. Several criteria are described for determination of second primary or metastatic disease, but none of these is certain.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival at 10 years is 95% in patients under 40 years of age and 75% in older patients. 15 Despite the presence of distant metastases, the patients frequently survive for several years without treatment. Lung is the most common site of metastasis followed by bone.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…Papillary thyroid cancer is commonly associated with lymphatic spread to regional lymph nodes. Distant metastases occur more rarely, usually involving the lungs and bone (1–7% of patients) ( 14 ), but occasionally occurs in the brain, sphenoid sinus, orbit, adrenal, kidney and ovary ( 15 18 ). A retrospective review of the literature revealed only two case reports of muscle metastases arising from PTC ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that skeletal muscle is a hostile environment for proliferating cancer cells, due to muscle motion and unadapted muscle pH ( 19 ), which may explain the lack of such cases. Synchronous lung and skeletal muscle disease from PTC is an extremely rare manifestation ( 18 ). To the best of our knowledge, only two cases have been previously reported ( Table I ).…”
Section: Discussionmentioning
confidence: 99%